Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Pengguna Shopee Di Simokalangan II Surabaya - Bagus Suryo Sajiwo; Iswati Iswati; Is Fadhillah; Handy Ariwibowo (Master Manajemen, 2024)
This study aims to analyze the effect of price and promotion on purchasing decisions. The research method used is a quantitative method. This study uses purposive sampling. The sample in this study amounted to 50 respondents. Data collection instrument using a questionnaire. The dependent variable is the purchase decision variable and the independent variable is the price, and the promotion is the price, and the promotion is on the purchase decision of Shopee users. The data analysis method used is multiple linear regression. All statements are valid, reliable and normal. The results show that the coefficient of determination (R Square) of the independent variable on the dependent variable is R2 = 0.507 or 50.7%. The independent variable can explain the dependent variable. From the research, it shows that price has a significant effect on purchasing decisions of Shopee users in Simokalangan II. This is proven by tcount being greater than ttable (3,722 > 1,678). And so does the Promotion which has a significant effect on the purchasing decision of Shopee users in Simokalangan II. This is evidenced by tcount being greater than ttable (4,221 > 1,678). While the results of the simultaneous test of price and promotion variables have a significant effect of fcount 24.120 > ftable 2.802 on purchasing decisions. This shows that the better the price and promotions provided, the higher the buying decision of Shopee users in Simokalangan II.